An urban approach to planetary boundaries - Hoornweg, Daniel; Hosseini, Mehdi; Kennedy, Christopher; Behdadi, Azin (Ambio, 2016)
The achievement of global sustainable development goals subject to planetary boundaries will mostly be determined by cities as they drive cultures, economies, material use, and waste generation. Locally relevant, applied and quantitative methodologies are critical to capture the complexity of urban infrastructure systems, global inter-connections, and to monitor local and global progress toward sustainability. An urban monitoring (and communications) tool is presented here illustrating that a city-based approach to sustainable development is possible. Following efforts to define and quantify safe planetary boundaries in areas such as climate change, biosphere integrity, and freshwater use, this paper modifies the methodology to propose boundaries from a city's perspective. Socio-economic boundaries, or targets, largely derived from the Sustainable Development Goals are added to bio-physical boundaries. Issues such as data availability, city priorities, and ease of implementation are considered. The framework is trialed for Toronto, Shanghai, Sao Paulo, Mumbai, and Dakar, as well as aggregated for the world's larger cities. The methodology provides an important tool for cities to play a more fulsome and active role in global sustainable development.